Novel reconstruction method using long and narrow gastric tube in laparoscopic proximal gastrectomy for cancer: a retrospective case series study - Ueda, Yoshitake; Kawasaki, Takahide; Tanabe, Sanshi; Suzuki, Kosuke; Ninomiya, Shigeo; Etoh, Tsuyoshi; Inomata, Masafumi; Shiraishi, Norio (Frontiers in Surgery, 2024)
Background and Objectives: To clarify the safety and feasibility of laparoscopic proximal gastrectomy (LPG) with our novel reconstruction methods.Methods: Novel method is a reconstruction with a long and narrow gastric tube with widening of the proximal side created by linear stapler, and esophagogastrostomy is performed by linear stapler. In conventional method, esophagogastrostomy is performed by a circular stapler. Shortand long-term outcomes of a novel method were compared with those of conventional method.Results: A total of 44 patients whom LPG was performed were enrolled in this retrospective study. No cases of anastomotic leakage and stenosis were observed in both groups. The cases of postoperative reflux esophagitis (Grade B or higher) at 1 year after operation in the Novel group were less than those in the Conventional group (17% vs. 44%).Conclusion: LPG with novel reconstruction method can be easily performed, and may be feasible for the treatment of proximal gastric cancer.